Regulatory Modules Involved in the Degradation and Modification of Host Cell Walls During Cuscuta campestris Invasion - Yokoyama, Ryusuke; Yokoyama, Toshiya; Kuroha, Takeshi; Park, Jihwan; Aoki, Koh; Nishitani, Kazuhiko (Frontiers in Plant Science, 2022)
Haustoria of parasitic plants have evolved sophisticated traits to successfully infect host plants. The degradation and modification of host cell walls enable the haustorium to effectively invade host tissues. This study focused on two APETALA2/ETHYLENE RESPONSE FACTOR (ERF) genes and a set of the cell wall enzyme genes principally expressed during the haustorial invasion of Cuscuta campestris Yuncker. These orthogroups have been implicated in cell wall enzyme activities in the abscission of tomatoes, which are close relatives of Cuscuta species. Although haustoria are generally thought to originate from root tissues, our results suggest that haustoria have further optimized invasion potential by recruiting regulatory modules from other biological processes.